Buddhist Non-conceptualism: Building a Smart Border Wall. - Siderits, Mark (Philosophy East & West: A Quarterly of Comparative Philosophy, 2020)
The article examines Indian Buddhist scholar Dignaga's views on conceptually mediated inference and concept-free perception. Topics covered include the reason behind the bad reputation conceptualization has in Buddhism, the connection between a cognition's clarity and the British empiricists' doctrine of ideas, and the dispute between conceptualists and non-conceptualists about perception.